The Correlation Of Nurses Compotence With Implementation Strategic Of Sesion 3 Toward High Risk Of Physical Abuse Patient In Madani General Hospital, Central Sulawesi Province : competence of nurse - Sindy Ayu Anggraeni; Wahyu Sulfian; Sukrang (Politeknik Karya Persada Muna, 2021)
Background: Physical abuse is main problem in society toward mental disorder pateint. The prevention effort for physical abuse need nurses compotence with implementation strategic of sesion 3 toward high risk of physical abuse. The purpose of research to analyse the correlation of nurses compotence with implementation strategic of sesion 3 toward high risk of physical abuse in Madani General Hospital, Central Sulawesi Province Method: This is quantitative research with cross sectional design. The total of population is 30 staff nurses in Manggis, Salak, and Sarikaya Ward of Madani General Hospital, Central Sulawesi Province and sampling taken by total population sampling technique. This research analysed by univariate and bivariate analyses Results: The result of fisher’s exact test found p value =0,000 (p Value <0,05), it means statistically that have correlation between nurses compotence with implementation strategic of sesion 3 toward high risk of physical abuse. Conclusions: mentioned that have correlation of nurses compotence with implementation strategic of sesion 3 toward high risk of physical abuse in Madani General Hospital, Central Sulawesi Province. Keywords: compotence, nurses, physical abuse